Application of the microfluidic-assisted replication track analysis to measure DNA repair in human and mouse cells - Welcsh, Piri (Methods, 2016)
Functional studies of the roles that DNA helicases play in human cells have benefited immensely from DNA fiber or single molecule technologies, which enable us to discern minute differences in behaviors of individual replication forks in genomic DNA in vivo. DNA fiber technologies are a group of methods that use different approaches to unravel and stretch genomic DNA to its contour length, and display it on a glass surface in order to immuno-stain nucleoside analog incorporation into DNA to reveal tracks (or tracts) of replication. We have previously adopted a microfluidic approach to DNA stretching and used it to analyze DNA replication. This method was introduced under the moniker maRTA or microfluidic assisted Replication Track Analysis, and we have since used it to analyze roles of the RECQ helicases WRN and BLM, and other proteins in normal and perturbed replication. Here we describe a novel application of maRTA to detect and measure repair of DNA damage produced by three different agents relevant to etiology or therapy of cancer: methyl-methanesulfonate, UV irradiation, and mitomycin C. Moreover, we demonstrate the utility of this method by analyzing DNA repair in cells with reduced levels of WRN or of the base excision repair protein XRCC1.